Findings of spiders in vineyards of Northern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The research regarded the specific composition of spider fauna collected in vineyardsof two areas of Northern Italy (territory of Ghemme in Novara provinceand vineyards in Brescia province) using pitfall-traps in the course of two vegetativeseasons (1993 and 1994). Specimens of 73 species were collected, somepresent in both areas, some in one only. That is nearly the 5% of the species recordedfrom Italy in the Checklist of the Italian fauna species, witnessing a goodpresence of spiders, important natural predators.
Keywords: Spider fauna,; vineyards; Northern Italy